Deep-level defects in n-type GaAsBi alloys grown by molecular beam epitaxy at low temperature and their influence on optical properties. Issue 1 (December 2017) - Gelczuk, Łukasz; Kopaczek, Jan; Rockett, Thomas B. O.; Richards, Robert; Kudrawiec, Robert
Abstract Deep-level defects in n-type GaAs1−x Bix having 0 ≤ x  ≤ 0.023 grown on GaAs by molecular beam epitaxy at substrate temperature of 378 °C have been injvestigated by deep level transient spectroscopy. The optical properties of the layers have been studied by contactless electroreflectance and photoluminescence. We find that incorporating Bi suppresses the formation of GaAs-like electron traps, thus reducing the total trap concentration in dilute GaAsBi layers by over two orders of magnitude compared to GaAs grown under the same conditions. In order to distinguish between Bi- and host-related traps and to identify their possible origin, we used the GaAsBi band gap diagram to correlate their activation energies in samples with different Bi contents. This approach was recently successfully applied for the identification of electron traps in n-type GaAs1−x Nx and assumes that the activation energy of electron traps decreases with the Bi (or N)-related downward shift of the conduction band. On the basis of this diagram and under the support of recent theoretical calculations, at least two Bi-related traps were revealed and associated with Bi pair defects, i.e. (VGa +BiGa )−/2− and (AsGa +BiGa )0/1− . In the present work it is shown that these defects also influence the photoluminescence properties of GaAsBi alloys.